Factors influencing attitudes toward xenotransplantation clinical trials: A report of focus group studies. (7th March 2021) - Hurst, Daniel J.; Padilla, Luz A.; Cooper, David K. C.; Paris, Wayne
Abstract: Background: Clinical trials of xenotransplantation (XTx, ie, cross‐species transplantation, specifically the transplantation of genetically engineered pig organs into human recipients) are due to start within a few years. Methods: Five focus groups were conducted in April‐May 2019, among local religious leaders (N = 10), organ procurement staff/administrators (N = 5), patients and parents of patients who may need an organ transplant or are transplant recipients (N = 9), and local businesspersons in the community (N = 3). Groups were audio‐recorded, transcribed, and analyzed with NVivo software to identify themes of participants' thoughts to XTx. Results: An overall Cohen's kappa statistic of 0.71 was established. In general, there was wide agreement among participants that XTx is an exciting and acceptable option to explore as an organ alternative. Concerns were expressed primarily regarding issues of animal ethics, stigma regarding how pigs are viewed in society, organ allocation logistics, quality of life after receiving a xenograft, and how XTx would be accepted by certain theological traditions. Conclusion: Overall, various stakeholders accepted XTx as a clinical option. However, there were ethical, social, and physical concerns raised. Future studies exploring the development of education strategies that may help alleviate concerns related to XTx before it becomes a clinical alternative are needed among the general public, potential XTx candidates, and their family members.